A fuzzy multiple objective decision support model for energy-economy planning - Borges, Ana Rosa; Antunes, Carlos Henggeler (European journal of operational research, 2003)
In this paper an interactive approach to deal with fuzzy multiple objective linear programming problems is presented, which is based on the analysis of the decomposition of the parametric (weight) diagram into indifference regions corresponding to basic efficient solutions. This approach is illustrated to tackle uncertainty and imprecision associated with the coefficients of an input–output energy-economy planning model, aimed at providing decision support to decision makers in the study of the interactions between the energy system and the economy on a national level.